Reconstruction of Wave-Particle Duality and its Implications for General Chemistry Textbooks - Niaz, Mansoor; Marcano, Cecilia; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
It goes without saying that atomic structure, including its dual wave-particle nature, cannot be demonstrated in the classroom. Thus, for most science teachers, especially those in physics and chemistry, the textbook is their key resource and their students core source of information. Science education historiography recognizes the role played by the history and philosophy of science in developing the content of our textbooks, and with this in mind, the authors analyze more than 120 general chemistry textbooks published in the USA, based on criteria derived from a historical reconstruction of wave-particle duality. They come to some revealing conclusions, including the fact that very few textbooks discussed issues such as the suggestion, by both Einstein and de Broglie, and before conclusive experimental evidence was available, that wave-particle duality existed. Other large-scale omissions included de Broglie s prescription for observing this duality, and the importance of the Davisson-Germer experiments, as well as the struggle to interpret the experimental data they were collecting. Also untouched was the background to the role played by Schrödinger in developing de Broglie s ideas. The authors argue that rectifying these deficiencies will arouse students curiosity by giving them the opportunity to engage creatively with the content of science curricula. They also assert that it isn t just the experimental data in science that matters, but the theoretical insights and unwonted inspirations, too. In addition, the controversies and discrepancies in the theoretical and experimental record are key drivers in understanding the development of science as we know it today.
Introduction: A Brief Review of Textbook Analyses based on a History and Philosoph of Science Perspective -- Historical Reconstruction of Wave-Particle Duality -- Criteria for Evaluation of General Chemistry Textbooks -- Evaluation of General Chemistry Textbooks: Results and Discussion -- Conclusions and Educational Implications -- References -- Appendix A List of General Chemistry Textbooks Analyzed in this Study (n=128) -- Appendix B Reliability of Evaluation of General Chemistry Textbooks based on Inter-Rater Agreement.
Keywords: Education; Science -- History; Science -- Philosophy; Science -- Study and teaching; Education; Science Education; Teaching and Teacher Education; Learning & Instruction; History of Science; Philosophy of Science